Continuous speech speaker recognition based on CNN - Zhendong WU; Shucheng PAN; Jianwu ZHANG (Dianxin kexue)
In the last few years, with the constant improvement of the social life level, the requirement for speech recognition is getting higher and higher. GMM-HMM (Gaussian mixture-hidden Markov model) have been the main method for speaker recognition. Because of the bad modeling capability of big data and the bad performance of robustness, the development of this model meets the bottleneck.In order to solve this question, researchers began to focus on deep learning technologies. CNN deep learning model for continuous speech speaker recognition was introduced and CSR-CNN model was put forward. The model extracts fixed-length and right-order phonetic fraction to form an ordered sound spectrograph. Then input the voiceprint extract from CNN model to a reward-penalty function to continuous measurement. Experimental results show that CSR-CNN model has very good recognition effectin continuous speech speaker recognition field.